2010
DOI: 10.1177/0266242610383790
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial equity financing and securities regulation: An empirical analysis

Abstract: To protect investors, securities regulation generally restrains entrepreneurial ventures from entering the stock market. Scholars and regulators contend that strong rules and requirements for listing are essential to prevent the market from failing. However, these constraints can also unduly impede the growth of new ventures. We use the Canadian case to examine the effects of the relaxation of the regulatory constraints. Unlike in other countries, firms in Canada can list at a very early stage, without revenue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Therefore, analysing the Canadian situation of angel exit is particularly interesting. Canada enables firms to access a venture stock exchange at an early stage of development (Carpentier and Suret, 2012); in addition, the main stock market is easily accessible. The median gross proceeds of firms listing on the TSX venture exchange (TSXV) from 1997 to 2011 were CAN$1.6m, close to the total amount of Canadian angel deals, and most firms list before reporting any revenues.…”
Section: Classical Perspectivementioning
confidence: 99%
“…Therefore, analysing the Canadian situation of angel exit is particularly interesting. Canada enables firms to access a venture stock exchange at an early stage of development (Carpentier and Suret, 2012); in addition, the main stock market is easily accessible. The median gross proceeds of firms listing on the TSX venture exchange (TSXV) from 1997 to 2011 were CAN$1.6m, close to the total amount of Canadian angel deals, and most firms list before reporting any revenues.…”
Section: Classical Perspectivementioning
confidence: 99%
“…It is worth noting that the decline in the number of small IPOs in the United States since 2000 is blamed on excessive regulation by the Sarbanes-Oxley Act and the SEC Fair Disclosure Regulation (Gao et al, 2013). Recognizing that code can be burdensome for SMEs has led to the emergence of equity markets with lower admission requirements and disclosure rules specifically targeted at SMEs, such as the Euronext Free Exchange (Carpentier and Suret, 2010). The issue of financial disclosure by SMEs listed on a semi-regulated market was held by Lardon and Deloof (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, D'Aventi () and Cohen and Dean () identified the top management team of a firm as a market signal of reputation. Higgins and Gulati () and Carpentier and Suret () found that top management team can have positive effects on investor decisions. Chandler and Jansen (), Chandler and Hanks (), and Mitchelmore and Rowley () observed that a founder's entrepreneurial competencies are relevant to a successful new venture.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%